KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS VI SD NEGERI 05 LANDAU TUBUN - Suandi, Suandi; Ason, Ason; Atmaja, Muh Kusuma (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
The research background is that students have difficulty understanding the contents reading of the, when the teacher asks the contents of the reading texs students cannot answer, students have difficulty conveying their thoughts, students have difficulty on stringing words into complete sentences in concluding the contents of the reading. The aim of the studi was to determine students’ reading comprehesion ability in learning indonesia in grade VI of the State Elementary School 05 Landau Tubun. The research method uses a qualitative descriptive qualitative approach. Data collection  techniques using tests and interviews. Data  analysis using data reduction, data collection, verification, and conclusion. The results of the research on students’ reading comprehension skills in learning  Indonesia showed that students’ reading ebilities were in the sufficient category. This can be seen from the everage overall score of 13 students who scored in the range  0f 56-75 as many as 6 students with an average score 57.38 and a percentage of 61.53%. Only 1 students Students got a very a good category in the 86-100 range with a score of 86-84 and a percentage  of 7.6%. Studen got a good category in the score range 76-85, namely 1 peson with a score of 76.31 and a percentahge of 7.6%. Studen get less categories in the rangge 10-55, namely 5 people with a percentage of 38.46. Tush the ability to read comprehension of students in learning Indonesia in c grade VI of the state Elementary School 05 Landau Tubun included in the sufficent category because of the lack of vocabulary mastery in students